2014
DOI: 10.7717/peerj.534
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low and high dose intraarticular tiludronate on synovial fluid and clinical variables in healthy horses—a preliminary investigation

Abstract: To determine effects of intraarticularly administered tiludronate on articular cartilage in vivo, eight healthy horses were injected once with tiludronate (low dose tiludronate [LDT] 0.017 mg, n = 4; high dose tiludronate [HDT] 50 mg, n = 4) into one middle carpal joint and with saline into the contralateral joint. Arthrocentesis of both middle carpal joints was performed pre-treatment, and 10 min, 24 h, 48 h, 7 and 14 days after treatment. Synovial nucleated cell counts and total solids, tiludronate, sulfated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…However, these findings have not yet been confirmed in vivo. Synovial fluid tiludronate concentrations >2,000,000 ng/ml after intraarticular administration of 50 mg tiludronate into equine middle carpal joints were not associated with worse cartilage histology scores or decreased proteoglycan content at two weeks after treatment when compared to saline treated joints in four horses ( Duesterdieck-Zellmer et al, 2014 ). Nevertheless, tiludronate treated joints showed temporarily increased proteoglycan degradation and amelioration of increases in aggrecan synthesis compared to control joints, as determined by synovial fluid biomarkers.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, these findings have not yet been confirmed in vivo. Synovial fluid tiludronate concentrations >2,000,000 ng/ml after intraarticular administration of 50 mg tiludronate into equine middle carpal joints were not associated with worse cartilage histology scores or decreased proteoglycan content at two weeks after treatment when compared to saline treated joints in four horses ( Duesterdieck-Zellmer et al, 2014 ). Nevertheless, tiludronate treated joints showed temporarily increased proteoglycan degradation and amelioration of increases in aggrecan synthesis compared to control joints, as determined by synovial fluid biomarkers.…”
Section: Discussionmentioning
confidence: 91%
“…Tiludronate analysis was performed as previously described ( Duesterdieck-Zellmer et al, 2014 ) using high performance liquid chromatography (XBridge phenyl column, Waters, Milford, Massachusetts, USA) followed by mass spectrometry (API 4000; Applied Biosystems, Grand Island, New York, USA) . Briefly, tiludronate in all samples was methylated with 0.2 M trimethylsilyldiazomethane in acetone.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, intravenous administration of tiludronic acid is frequently used for the treatment of navicular disease or distal tarsal joint osteoarthritis and it has been demonstrated to be a successful therapy for these diseases in some horses. On the other hand, studies have shown that tiludronate also exerts some direct effects on cartilage and chondrocytes (Duesterdieck-Zellmer et al 2012, Duesterdieck-Zellmer et al 2014. Detrimental effects on cartilage and chondrocytes have been observed as the result of high synovial fluid tiludronate concentration (Duesterdieck-Zellmer et al 2012, Duesterdieck-Zellmer et al 2014) hence extra-label administration of tiludronate such as via regional limb perfusion or intraarticular injection may be harmful dependent on the dose used.…”
Section: Resultsmentioning
confidence: 99%
“…There are many mechanisms of therapeutic action in OA [29,30]: bisphosphonates may stabilise the subchondral bone or even protect chondrocytes from undergoing apoptosis. and the drug will enter the systemic circulation from this route [32]. In both man and horses, it is generally accepted that bisphosphonates can result in amelioration of clinical signs dues to OA [3,7,31].…”
mentioning
confidence: 99%
“…Tiludronate is also known to induce synovial inflammation when administered i.a. and the drug will enter the systemic circulation from this route [32]. Systemic or low dose i.v.…”
mentioning
confidence: 99%